PROSES BERPIKIR REFLEKTIF SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI SISTEM PERSAMAAN LINEAR DUA AVRIABEL - Ariestyan, Yola; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2016)
Abstract. An activity or thinking process that undertaken to make someone able to solve a mathematics problem have relation with the ability to remember, recognizing the relationship between mathematical concepts, so that it can bring up a new idea in making conclusion appropriately. Therefore, thinking reflectively is an ability to connect the knowledge that he get with his old knowledge, so that there is a conclusion to solve a new problem. This research was to describe student’s reflective thinking in solving mathematics problem for linear equation system with two variables. This research used qualitative descriptive research with the students of VIII A Class at SMP Negeri 4 Jember as the research subject. Intsrument that was used were written test in the form of 5 description questions and interview guidelines. From 32 students of VIII A class who took the test there were 5 students who followed the interview. The five subjects was students who fulfill all of reflective thinking indicators then to be subjected for the research. Based on the research it was obtained a result that from five students there were four subjects who were able to think reflectively in solving mathematic questions and one subject was able enough to think reflectively in solving mathematic question Keyword: Thinking Reflectively, Solving Mathematics problem